A 0.6-protamine/heparin ratio in cardiac surgery is associated with decreased transfusion of blood products. (4th July 2020) - Goedhart, Anne L M; Gerritse, Bastiaan M; Rettig, Thijs C D; van Geldorp, Martijn W A; Bramer, Sander; van der Meer, Nardo J M; Boonman-de Winter, Leandra J; Scohy, Thierry V
Abstract: OBJECTIVES: In cardiac surgery, adequate heparinization is necessary to prevent thrombus formation in the cardiopulmonary bypass (CPB). To counteract the heparin effect after weaning from CPB, protamine is administered. The optimal protamine/heparin ratio is still unknown. METHODS: In this before–after study, we evaluated the effect of a 0.6/1-protamine/heparin ratio implementation as of May 2017 versus a 0.8/1-protamine/heparin ratio on the 12-h postoperative blood loss and the amount of blood and blood component transfusions (fresh frozen plasma, packed red blood cells, fibrinogen concentrate, platelet concentrate and prothrombin complex concentrate) after cardiac surgery. A total of 2051 patients who underwent cardiac surgery requiring CPB between May 2016 and May 2018 were included. RESULTS: In the 0.6/1-protamine/heparin ratio group, only 28.8% of the patients received blood component transfusion, compared to 37.9% of the patients in the 0.8/1-ratio group ( P < 0.001). The median 12-h postoperative blood loss was 230 ml (interquartile range 140–320) in the 0.6/1-ratio group versus 260 ml (interquartile range 155–365) in the 0.8/1-ratio group ( P < 0.001). CONCLUSIONS: A 0.6/1-protamine/heparin ratio after weaning from CPB is associated with a significantly reduced 12-h postoperative blood loss and blood components transfusion.